Flushing versus not flushing the interface during small‐incision lenticule extraction. Issue 5 (May 2019) - Kind, Ralf; Kiraly, Laszlo; Taneri, Suphi; Troeber, Leonie; Wiltfang, Rainer; Bechmann, Martin; Meyer, Bertram; Greene, Brandon; Sekundo, Walter
Abstract : Purpose : To assess the differences in outcomes between interface flushing with a balanced salt solution after refractive lenticule removal in simultaneous uneventful bilateral small‐incision lenticule extraction (SMILE). Setting : Six study centers in Germany. Design : Prospective case series. Methods : Patients with myopia or myopic astigmatism of similar magnitude in both eyes with a spherical equivalent less than or equal to 10.0 diopters (D), preoperative corrected distance visual acuity (CDVA) of 0.80 decimal or better, and anisometropia less than or equal to 2.0 D were enrolled and followed for 3 months. One eye of each patient was treated with interface flushing after dry extraction of the lenticule. Flushing was performed with 1.0 cc balanced salt solution using a single‐use 27‐gauge cannula. The uncorrected distance visual acuity (UDVA) at 1 day, 1 week, and 3 months; the CDVA at 3 months; and postoperative differences at the slitlamp examination were recorded. Statistical analyses were performed with logarithm of the minimum angle of resolution values using paired t tests. The P value for significance was less than 0.05. Results : The study analyzed 470 eyes. One day postoperatively, the mean UDVA was 0.81 in the non‐flush group and 0.83 in the flush group ( P = .110). At the last visit 3 months postoperatively, the mean UDVA was 1.04 and 1.05, respectively ( P = .172). No significant differences in the rate of postoperative complications were found. Conclusion : Interface irrigation with 1.0 cc of balanced salt solution after the removal of the refractive lenticule has neither advantages nor disadvantages in terms of visual recovery, postoperative complications, or final visual acuity.